Interaction of Sleep and Cortical Structural Maintenance From an Individual Person Microlongitudinal Perspective and Implications for Precision Medicine Research - Wall, John; Xie, Hong; Wang, Xin (Frontiers in Neuroscience, 2020)
Sleep and maintenance of brain structure are essential for continuity of a person’s cognitive/mental health. Interestingly, whether normal structural maintenance of the brain and sleep continuously interact in some way over day-week-month times has never been assessed at an individual person level. This study used unconventional microlongitudinal sampling, structural magnetic resonance imaging, and n-of-1 analyses to assess normal interactions between fluctuations in structural maintenance of cerebral cortical thickness and sleep duration for day, week, and multi-week intervals over a 6 month period in a healthy adult man. Correlation and time series analyses provided indications of “if-then”, i.e. “if” this preceded “then” this followed, sleep-to-thickness maintenance and thickness maintenance-to-sleep bidirectional inverse interactions. Inverse interaction patterns were characterized by concepts of graded influences across nights, bilaterally positive relationships, continuity across successive weeks, and longer delayed/prolonged effects in the thickness maintenance-to-sleep than sleep-to-thickness maintenance direction. These interactions are proposed to involve normal circadian/allostatic/homeostatic mechanisms that continuously influence, and are influenced by, cortical substrate remodeling/turnover and sleep/wake cycle. Understanding interactions of individual person “-omics” is becoming a central interest in precision medicine research. The present n-of-1 findings contribute to this interest, and have implications for precision medicine research use of a person’s cortical structural and sleep “-omics” to optimize continuous maintenance of that individual’s cortical structure, sleep, and cognitive/mental health.